Implementasi Pendidikan Agama Hindu Perspektif Tri Hita Karana - I Nengah Arimbawa; I Nengah Adi Widana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2023)
Tri Hita Karana is a Balinese philosophy that conceptualizes harmony between Man and God, Man with Man, and Man with the Environment. Hindu Education basically aims to grow, develop and improve sradha (faith) and bhakti (devotion) of students towards Ida Sang Hyang Widhi Wasa through training, appreciation, and practice of Hindu teachings, so that they become Hindu people who are dharmika and able to realize the noble ideals of Moksartham Jagadita. This is very much in line with the objectives of National Education, as stated in the National Education System Law No. 20 of 2003. Thus, the Tri Hita Karana philosophy can contribute to the goals of Hindu Education in particular and the goals of National Education in general.Keywords:implementation, Hindu Religious, Tri Hita Karana